2020
DOI: 10.3390/biom10121693
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ferrous Sulfate (FeSO4) in Resistance to Cadmium Stress in Two Rice (Oryza sativa L.) Genotypes

Abstract: The impact of heavy metal, i.e., cadmium (Cd), on the growth, photosynthetic pigments, gas exchange characteristics, oxidative stress biomarkers, and antioxidants machinery (enzymatic and non-enzymatic antioxidants), ions uptake, organic acids exudation, and ultra-structure of membranous bounded organelles of two rice (Oryza sativa L.) genotypes (Shan 63 and Lu 9803) were investigated with and without the exogenous application of ferrous sulfate (FeSO4). Two O. sativa genotypes were grown under different level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 93 publications
1
30
0
Order By: Relevance
“…The increase in the activities of antioxidant enzymes was concomitant with the generation of extra ROS [62,72,73]. It was also reported that increases in the activities of various antioxidant enzymes under environmental stress conditions are due to the reduction in glutathione con-tents [74,75]. In the current experiment, oxidative stress biomarkers were enhanced in maize seedlings cultivated in a minimal water containing environment (Figure 5), while the water deficient environment also increased the antioxidants activity in drought, with respect to the control seedlings (Figure 6).…”
Section: Discussionmentioning
confidence: 94%
“…The increase in the activities of antioxidant enzymes was concomitant with the generation of extra ROS [62,72,73]. It was also reported that increases in the activities of various antioxidant enzymes under environmental stress conditions are due to the reduction in glutathione con-tents [74,75]. In the current experiment, oxidative stress biomarkers were enhanced in maize seedlings cultivated in a minimal water containing environment (Figure 5), while the water deficient environment also increased the antioxidants activity in drought, with respect to the control seedlings (Figure 6).…”
Section: Discussionmentioning
confidence: 94%
“…Cobalt is a vital trace metal, required by some specific plants for certain biochemical attributes and metabolism [14]. Some reports showed its importance in the legumes for root functions and biological nitrogen fixation via root nodules [15]. Small quantities of Co might be beneficial for plants and animals; however, higher concentration is toxic for the plant-soil-water-animal nexus that can produce adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ -ATPase activity is another key analysis to examine the integrity of protein molecules during frozen storage [ 2 , 27 , 28 ]. Figure 2 shows the Ca 2+ -ATPase activity of all MP samples during frozen storage.…”
Section: Resultsmentioning
confidence: 99%